1998
DOI: 10.1161/01.cir.97.7.703
|View full text |Cite
|
Sign up to set email alerts
|

Primary Malignant Fibrous Histiocytoma of the Heart Treated With Orthotopic Heart Transplantation

Abstract: A 24-year-old white man presented with dyspnea and fatigue. Physical examination revealed hepatosplenomegaly. A chest roentgenogram showed small pleural effusions without infiltrates. Ultrasound examination revealed ascites of the abdomen and pelvis and echogenic liver vessels that suggested congestive heart failure. A nuclear magnetic resonance image of the chest ( Fig 1A) showed a 4ϫ6-cm mass occupying the right ventricle. The mass filled the apex and obstructed the right ventricular cavity. A computerized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Radiologic Features.-The most common radiographic abnormality in patients with cardiac sarcoma is cardiomegaly. Other findings include heart failure, pleural effusion, focal cardiac mass, pulmonary consolidation, and pericardial effusion (2,7,91,(94)(95)(96). Because of their location, the radiographic findings of left atrial sarcomas can mimic those of left atrial myxoma.…”
Section: Malignant Neoplasms Sarcomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiologic Features.-The most common radiographic abnormality in patients with cardiac sarcoma is cardiomegaly. Other findings include heart failure, pleural effusion, focal cardiac mass, pulmonary consolidation, and pericardial effusion (2,7,91,(94)(95)(96). Because of their location, the radiographic findings of left atrial sarcomas can mimic those of left atrial myxoma.…”
Section: Malignant Neoplasms Sarcomasmentioning
confidence: 99%
“…Even after complete tumor excision, however, local recurrence and metastatic disease occur frequently and early, usually within 1 year (2,90,94). Heart transplantation has been performed in some patients with unresectable cardiac sarcoma with satisfactory results (92,95,100). Chemotherapy and radiation therapy have not proved beneficial for the treatment of affected patients (92).…”
Section: Malignant Neoplasms Sarcomasmentioning
confidence: 99%
“…A second operation was not indicated in our patient because of the tumor dissemination into the chest wall. It has been reported that heart transplantation offers good results for cardiac malignancies (45,57), however the indication is considered to be strictly limited due to the highly metastatic potential. In summary,we presented a rare case of cardiac MFH and reviewed 46 additional cases in order to clarify the nature of this rare disease.…”
Section: Treatment and Prognosismentioning
confidence: 99%